The influence of feeding enrichment on the behavior of small felids (Carnivora: Felidae) in captivity - Letícia S. Resende; Gabriella L. Remy; Valdir de Almeida Ramos Jr; Artur Andriolo (Zoologia (Curitiba), 2009)
Animals in captivity are frequently exposed to environmental deprivation resulting in abnormal behaviors that indicate distress. The aim of the present study was to evaluate the effect of the "surprise pack" environmental enrichment technique in improving the welfare of small neotropical felids in captivity. In order to accomplish this, we used five individuals from the Rio de Janeiro Zoo. The experiment was divided into three steps corresponding to: I) period prior to the enrichment, II) period in which the animals were being submitted to enrichment stimuli, and III) period after the enrichment. In phase II, we observed a significant reduction in abnormal behavior compared to phases I and III. Only in phase II did the animals demonstrate the following behaviors: predation, social interaction and territory demarcation. However, in this same phase, the mean time spent interacting with the enrichment throughout the day showed a decrease.